Endocannabinoid Modulation of Nucleus Accumbens Microcircuitry and Terminal Dopamine Release - Covey, Dan P.; Yocky, Alyssa G. (Frontiers in Synaptic Neuroscience, 2021)
The nucleus accumbens (NAc) is located in the ventromedial portion of the striatum and is vital to valence-based predictions and motivated action. The neural architecture of the NAc allows for complex interactions between various cell types that filter incoming and outgoing information. Dopamine (DA) input serves a crucial role in modulating NAc function, but the mechanisms that control terminal DA release and its effect on NAc neurons continues to be elucidated. The endocannabinoid (eCB) system has emerged as an important filter of neural circuitry within the NAc that locally shapes terminal DA release through various cell type- and site-specific actions. Here, we will discuss how eCB signaling modulates terminal DA release by shaping the activity patterns of NAc neurons and their afferent inputs. We then discuss recent technological advancements that are capable of dissecting how distinct cell types, their afferent projections, and local neuromodulators influence valence-based actions.